ANALISA PERTUMBUHAN DAN HASIL LABU MADU (Cucurbita moschata) DENGAN PEMANGKASAN CABANG DAN APLIKASI MACAM PUPUK ORGANIK CAIR - Mariyatul Qibtiyah; M. Alfan Fikri Fatoni; Dian Eka Kusumawati (Universitas Tribhuwana Tunggadewi, 2022)
This study aimed to determine the growth and production of butternut squash, through branch pruning and the application of goat biourin and POC of rice washing water. The first factor of pruning (P) consists of (P1) pruning branches 1-5, (P2) pruning branches 1-6, and (P3) pruning branches 1-7. The second factor is liquid organic fertilizer (C) consisting of: (C1) control, (C2) goat biourin, and (C3) POC of rice washing water. Each treatment combined into nine combinations of replications and repeated three times. The results showed that the combination of pruning branches 1-6 and goat biourin (P2C2) have a good effect on the growth of honey gourd. The best butternut squash yields were the combination of pruning branches 1-6 and POC of rice washing water (P2C3) with the highest fruit weight gain..